DOI: 10.35537/10915/4343
|View full text |Cite
|
Sign up to set email alerts
|

Volcanismo postcolapso de la caldera Vilama, Mioceno superior, Puna argentino-boliviana

Abstract: Este trabajo se realizó a partir de la hipótesis de trabajo: "los centros volcánicos emplazados alrededor y por encima del domo resurgente de la caldera Vilama (Puna argentina-Altiplano boliviano) con posterioridad a su colapso, son representantes de la Etapa de Postcolapso de dicha caldera". De acuerdo con el modelo clásico de calderas resurgentes, para cumplir con dicha condición los centros volcánicos deberían estar formados por rocas derivadas del magma restante en la cámara magmática luego de la erupción … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 128 publications
(216 reference statements)
0
4
0
Order By: Relevance
“…This feature is therefore interpreted to be brine-saturated crust. Furthermore, this feature is particularly interesting as it lies beneath Cerro Loromayo (Fracchia, 2009;Soler et al, 2007; Cerro Loromayo summit at intersection of the profiles CC' and DD' in Figure 2), a volcano that could have exhibited activity as late as 0.9 Ma (Fracchia, 2009). Based on our Q P /Q S results, this feature appears isolated, with no vertical column-like feature below it.…”
Section: Identifying and Mapping Fluids And Their Compositionmentioning
confidence: 60%
See 1 more Smart Citation
“…This feature is therefore interpreted to be brine-saturated crust. Furthermore, this feature is particularly interesting as it lies beneath Cerro Loromayo (Fracchia, 2009;Soler et al, 2007; Cerro Loromayo summit at intersection of the profiles CC' and DD' in Figure 2), a volcano that could have exhibited activity as late as 0.9 Ma (Fracchia, 2009). Based on our Q P /Q S results, this feature appears isolated, with no vertical column-like feature below it.…”
Section: Identifying and Mapping Fluids And Their Compositionmentioning
confidence: 60%
“…Isolated features with Q P /Q S > 1 also exist. One such feature, beneath Cerro Loromayo (Fracchia, 2009;Soler et al, 2007), is shown in detail in Figures 2d-2f (labeled C). This feature also corresponds to a region of low resistivity, as do other Q P / Q S > 1 regions.…”
Section: 1029/2022gl100974mentioning
confidence: 88%
“…Isolated features with Q P /Q S > 1 also exist. One such feature, beneath Cerro Loromayo (Fracchia, 2009;Soler et al, 2007), is shown in detail in Figures 2d-2f (labeled C). This feature also corresponds to a region of low resistivity, as do other Q P / Q S > 1 regions.…”
Section: Resultsmentioning
confidence: 96%
“…This feature is therefore interpreted to be brine‐saturated crust. Furthermore, this feature is particularly interesting as it lies beneath Cerro Loromayo (Fracchia, 2009; Soler et al., 2007; Cerro Loromayo summit at intersection of the profiles CC’ and DD’ in Figure 2), a volcano that could have exhibited activity as late as 0.9 Ma (Fracchia, 2009). Based on our Q P / Q S results, this feature appears isolated, with no vertical column‐like feature below it.…”
Section: Discussionmentioning
confidence: 99%